2021
DOI: 10.1007/s12072-021-10173-y
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic body radiotherapy versus intensity-modulated radiotherapy for hepatocellular carcinoma with portal vein tumor thrombosis

Abstract: Background: It is unclear whether robotic stereotactic body radiotherapy (SBRT) is superior to intensity-modulated radiotherapy (IMRT) in advanced hepatocellular carcinoma (HCC). This study aimed to compare the long-term outcomes of SBRT with those of IMRT in HCCs with portal vein tumor thrombosis (PVTT).Methods: We retrospectively evaluated 287 HCC patients with PVTT who underwent radiotherapy between January 2000 and January 2017. Of them, 154 and 133 patients were treated with IMRT and SBRT, respectively. O… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…Compared with 3D-CRT, IMRT provides a survival benefit in HCC with MVI (29). Meanwhile, a study showed median OS and LCR in the IMRT group were similar to those of the SBRT group for HCC with MVI (47). However, study about IMRT for HCC with MVI is scarce, and the clinical efficacy requires more clinical data to support.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with 3D-CRT, IMRT provides a survival benefit in HCC with MVI (29). Meanwhile, a study showed median OS and LCR in the IMRT group were similar to those of the SBRT group for HCC with MVI (47). However, study about IMRT for HCC with MVI is scarce, and the clinical efficacy requires more clinical data to support.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a retrospective analysis of 19 HCC patients with IVC thrombus treated with conventional RT or SBRT showed evidence that RT is feasible and safe with acceptable toxicity in this patient group [ 22 ]. SBRT was found to be non-inferior to IMRT regarding overall survival, progression-free survival, and local control with the additional advantage of decreased overall treatment duration [ 23 ]. Xi et al retrospectively evaluated 41 HCC patients with TT in either the portal vein or IVC treated with SBRT.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al reported that RT with a BED of 58 Gy 10 or higher improved tumor response and overall survival (OS) in HCC patients with PVTT. Li et al compared the treatment effect between IMRT and SBRT technique in HCC patients with PVTT; OS and progression-free survival were better when BED 100 Gy 10 or higher was prescribed, regardless of the technique (Li et al 2021). High BED RT could be considered as one of the treatment options that may improve tumor response and survival in HCC patients with PVTT.…”
Section: Discussionmentioning
confidence: 99%